A Study on the Actual Use of Digital Competence in the Practicum of Education Degree. - Guillén-Gámez, Francisco David; Mayorga-Fernández, María Josefa; Álvarez-García, Francisco J. (Springer, 2018)
Despite the existence of many programs and training projects in the field of ICT, in post-secondary education, the teaching and learning process continues to be supported by traditional classroom methods. This phenomenon can be particularly observed in education degrees, even though future teachers are expected to acquire the necessary digital skills in order to carry out their work properly. The purpose of this study is to explore in greater depth the use of 2.0 applications in the education training of future teachers, as well as to outline the different correlations between the use of these 2.0 tools and their perceived level of digital competence, age and their level of motivation. For it, a quasi-experimental, ex post facto research was carried out with a sample of 108 future teachers from the Faculty of Education, Pontifical University of Salamanca (UPSA). The results have shown that future teachers have a low level of attitude of use towards ICT in the classroom, with an average of 2.29 based on five points. Furthermore, the results have revealed that the level of digital competence and the motivation to use ICT are two variables that correlate positively, while other variables do not show any correlation, such as age.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/36187?template=romeo
Keywords: Tecnología educativa; Educación - Innovaciones tecnológicas; New methodologies; ICT competence; Future teacher; New technologies; Educational innovation